Beta-cell function and human islet transplantation: can we improve?. Issue 3 (March 2021) - Chen, Jennifer; Gunton, Jenny E
Abstract : Islet transplantation, a therapeutic option to treat type 1 diabetes, is not yet as successful as whole-pancreas transplantation as a treatment for diabetes. Mouse models are commonly used for islet research. However, it is clear disparities exist between islet transplantation outcomes in mice and humans. Given the shortage of transplant-grade islets, it is crucial that we further our understanding of factors that determine long-term islet survival and function post-transplantation. In turn, this may lead to new therapeutic targets and strategies that will improve transplant outcomes. Here, we summarise the current landscape in clinical transplantation, highlight underlying similarities and differences between mouse and human islets, and review interventions that are being considered to create a new pool of β-cells for clinical application.